Pengaruh Kemudahan Transaksi Dan Diskon Terhadap Loyalitas Pelanggan Serta Dampaknya Pada Kepuasan Pelanggan Pengguna Dana : Studi Kasus Pada Konsumen Toko Kanaya Ponsel & Brilink Di Sei Rampah - Arfah, Yenni; Cindranata , Yusen (STIE Bina Karya, 2024)
This research aims to determine the effect of ease of transactions and discounts on customer loyalty and its impact on customer satisfaction with Dana users. This research was conducted on Dana users at the Kanaya Mobile & Brilink Store located in Sei Rampah, Serdang Bedagai. This type of research is quantitative descriptive research. The research sample consisted of 96 respondents with sampling techniques using techniques purposive sampling. Research data was obtained using a Google Form questionnaire. The data analysis method uses the path analysis method with the help of the SPSS Statistics 25 analysis program. The research results show that: 1). Ease of transactions has a significant effect on customer satisfaction. 2). Discounts do not have a significant effect on customer satisfaction. 3). Ease of transactions has a significant effect on customer loyalty. 4). Discounts have a significant effect on customer loyalty. 5). Customer satisfaction has a significant effect on customer loyalty. 6). Satisfaction customers have an impact on the ease of transactions on customer loyalty 7). Customer satisfaction does not have an impact on discounts on customer loyalty.